Multi-resolution functional summarization and alignment of biological network models - Seah, Boon Siew (2014)
The desire to study biology from a systems perspective has led to an emergence of new science - biological networks analysis. Biological network models biological entities (e.g., proteins and genes) and their relationships (e.g., physical and genetic interactions) to characterize their cooperative activity within a system. With the rapid growth of network data, the information overload problem arises and human interpretation of such data becomes impossible. Hence, there is urgent need to construct methods for large-scale functional visualization of biological networks to understand the mechanics of biological systems.